ANALISIS KINERJA KEUANGAN BADAN USAHA DI BURSA EFEK INDONESIA SUB INDUSTRI JASA KESEHATAN DAN FARMASI SEBELUM DAN SAAT PANDEMI COVID-19 - Setiadi Alim Lim (Jurnal Akuntansi dan Pajak, 2022)
The Covid-19 pandemic has had a huge impact on the performance of the business sector. This study examines whether there are differences in financial performance between health service provider and pharmaceutical sub-industry companies listed on the Indonesia Stock Exchange (IDX), both before and during the Covid-19 pandemic. In addition, it is also investigated whether there are differences in the combined financial performance of health services provider and pharmaceutical company between before and during the Covid-19 pandemic. Financial performance is measured by financial ratios consisting of liquidity ratios, solvency ratios, profitability ratios, and measurement of growth rates. The results showed that there was only a significant difference for asset growth before the Covid-19 pandemic, while for the liquidity ratio, solvency ratio, profitability ratio, and other measured growth rates, there was no significant difference between health service providers and pharmaceutical sub-industry companies, both before and during the Covid-19 pandemic. In addition, the results of the study also show that there is no significant difference in financial performance including liquidity ratio, solvency ratio, profitability ratio, and growth rate of the combined companies of sub-industry providing health and pharmaceutical services when compared to conditions before the Covid-19 pandemic and during the Covid-19 pandemic.